Some characteristics of a group of coloured runaway boys aged 8 - 16 years and factors that these boys and their mother perceived as contributing to their runaway behavior - Jayes, Claire Sharman (Department of Social Development, 2015)
This study was of a group of street children who had run away from home. The writer sought to discover factors that led to their running away. Interviews were conducted with both the boys and their mothers (or mother substitutes). Interview schedules with both open-ended and closed questions were used to obtain certain demographic characteristics of the families, the runaway episodes and the causes for the runaway behaviour as perceived by the runaways and their mothers. The study revealed that multiple interrelated factors within the families, the boys and society seemed to contribute either directly or indirectly to their runaway behaviour. Homes were marked by conflict, instability, alcohol and physical abuse, deprivation and neglect. The runaways in turn responded to their stressful home life by running away. The runaways in contrast to their mothers, predominantly perceived factors within the home as causing them to leave home, whereas the mothers tended to externalize these causes to peer group influences.